Stereoselective, nitro-Mannich/lactamisation cascades for the direct synthesis of heavily decorated 5-nitropiperidin-2-ones and related heterocycles - Jakubec, Pavol; Cockfield, Dane M.; Helliwell, Madeleine; Raftery, James; Dixon, Darren J. (Beilstein Journal of Organic Chemistry, 2012)
A versatile nitro-Mannich/lactamisation cascade for the direct stereoselective synthesis of heavily decorated 5-nitropiperidin-2-ones and related heterocycles has been developed. A highly enantioenriched substituted 5-nitropiperidin-2-one was synthesised in a four component one-pot reaction combining an enantioselective organocatalytic Michael addition with the diastereoselective nitro-Mannich/lactamisation cascade. Protodenitration and chemoselective reductive manipulation of the heterocycles was used to install contiguous and fully substituted stereocentres in the synthesis of substituted piperidines.
Keywords: cascade; imine; Michael addition; nitro-Mannich; organocatalysis; piperidine alkaloids